The New England Journal of Medicine N° 12 (Owned Published, 2004)
Crossing the Species Barrier ù One Small Step to Man, One Giant Leap to MankindDecimal Point ù Osteoporosis Therapy at the 10-Year MarkEarthquake Relief ù The U.S. Medical Response in Bam, IranGod at the BedsideAvian Influenza A (H5N1) in 10 Patients in VietnamTen Years` Experience with Alendronate for Osteoporosis in Postmenopausal WomenA Randomized Trial of Chemoradiotherapy and Chemotherapy after Resection of Pancreatic CancerCurrent Concepts: ThrombocytosisMedical Progress: Acquired and Inherited LipodystrophiesEruptive Xanthomas Associated with Hypertriglyceridemia and New-Onset Diabetes MellitusAngiomatosis Associated with Sneddon`s SyndromeCase 9-2004 ù An 18-Year-Old Man with Respiratory Symptoms and ShockAdjuvant Therapy for Pancreatic Cancer ù The Debate ContinuesA Novel BRCA2-Binding Protein and Breast and Ovarian TumorigenesisChronic Allograft NephropathySurgeon Volume and Operative MortalityDysplastic NeviChronic ConstipationBody PackingTherapy for Irritable Bowel SyndromeRibavirin-Induced Pure Red-Cell Aplasia during Treatment of Chronic HepatitisViral Encephalitis in HumansThe Speckled Monster: A Historical Tale of Battling SmallpoxTextbook-Atlas of Intestinal Infections in AIDS